ANALISIS PERMINTAAN DAGING SAPI DI JAWA BARAT PERIODE 2003-2014 - Imaniyar, Revita; Siregar, Juarni (www.bsi.ac.id, 2015)
The Central Bureau of Statisticsis anon-departmental government agency directly responsibletothe President. This study aims to determine the factors that affectcattle demand for meat. Toanalyzethe influence of the price of beef, goat meat prices (competitors), and total population.. Toknow themagnitude of demand for beefin western Java. To obtain the data, the authorsobtain thedata fromBPS(Central Bureauof Statistics) ondemand for beef and mutton which is quitelargeamong the community.The method usedin this research is Multiple Linear Regression Analysis.From the results and discussion can be concluded that affect the price of beefper capitacalorieconsumption demand. Goatmeat prices (competitors) affect the demand for calorie consumptionper capita. The total population affect the demand percapita calorie consumption.Keywords: the price of beef, mutton prices, population